2021
DOI: 10.1002/ccr3.3912
|View full text |Cite
|
Sign up to set email alerts
|

Medulloblastoma in the cerebellopontine angle mimicking a schwannoma

Abstract: The typical distinction between cerebellopontine angle (CPA) medulloblastoma and other primary CPA tumors was not fully known. While CPA medulloblastoma is very uncommon, it should be included in the differential diagnosis of patients with CPA tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Following the application of chosen criteria, we found only 21 cases of medulloblastoma associated with auditory dysfunction 5,7,11,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] (Table 1). In this study, a gender predominance for male was found (52.3% males, 47.6% females); 38% of the patients were children and 62% of the patients were adults, with a mean age of 23 years (between 2 and 50 years).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following the application of chosen criteria, we found only 21 cases of medulloblastoma associated with auditory dysfunction 5,7,11,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] (Table 1). In this study, a gender predominance for male was found (52.3% males, 47.6% females); 38% of the patients were children and 62% of the patients were adults, with a mean age of 23 years (between 2 and 50 years).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that in some patients with hearing loss, tinnitus or dizziness, unexpectedly, the computer tomography scan of petrous bones did not show any lesion at the level of the internal auditory canal, but on the MRI examination, a lesion was noted in the cerebellopontine angle as a homogenous solid mass which appeared hyperintense on T2-weighted image 5,33 .…”
Section: Radiologic Criteria For Medulloblastomasmentioning
confidence: 97%
See 2 more Smart Citations